2020
DOI: 10.2174/1570159x17666191113103850
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of Central Nervous System Drainage Systems: Implications in the Context of Neurodegenerative Diseases

Abstract: : Until recently, it was thought that there were no lymphatic vessels in the central nervous system (CNS). Therefore, all metabolic processes were assumed to take place only in the circulation of the cerebrospinal fluid (CSF) and through the blood-brain barrier’s (BBB), which regulate ion transport and ensure the functioning of the CNS. However, recent findings yield a new perspective: There is an exchange of CSF with interstitial fluid (ISF), which is drained to the paravenous space and reaches lymphatic node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 73 publications
0
20
0
1
Order By: Relevance
“…Simple diffusion delivery (SDD) is another local brain drug delivery method that utilizes the concentration gradients to drive pharmaceutical agents to target zones via the brain ISS [135]. Since the brain ISS is divided into different segments based on brain ISF drainage [88,92,118,135], SDD has promise for delivering drugs to specific regions of the brain. However, before targeting drugs to brain regions through an SDD method, the tracerbased MRI technique may need to be used to ensure the brain ISF drainage in the area of the brain where the drug needs to be targeted.…”
Section: Iss As the Route Of Drug Delivery -Available Methods And Limmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple diffusion delivery (SDD) is another local brain drug delivery method that utilizes the concentration gradients to drive pharmaceutical agents to target zones via the brain ISS [135]. Since the brain ISS is divided into different segments based on brain ISF drainage [88,92,118,135], SDD has promise for delivering drugs to specific regions of the brain. However, before targeting drugs to brain regions through an SDD method, the tracerbased MRI technique may need to be used to ensure the brain ISF drainage in the area of the brain where the drug needs to be targeted.…”
Section: Iss As the Route Of Drug Delivery -Available Methods And Limmentioning
confidence: 99%
“…It is believed that blockage of brain ISF drainage accelerates the abnormal deposition of betaamyloid in AD, which contributes to both cerebral amyloid angiopathy and neurodegeneration [23,114,115]. Changes in the ISS have also been reported in other diseases, such as Parkinson's disease [116], multiple sclerosis [117,118], and epilepsy [17,119]. Moreover, another study in a mouse model of AD by Yue and associates suggested that the destruction of beta-amyloid deposits in the ECS using a light-emitting diode with red light facilitated not only the recovery of ISF drainage but also rescued cognitive function [15].…”
Section: Status Of Iss In Neurological Disordersmentioning
confidence: 99%
“…Increasing evidence supports the idea that the glymphatic system plays a central role in the clearance of macromolecular substances from the brain [22,23]. This model of glymphatic system has opened up new perspectives in understanding the pathogenesis of AD [49,50], stroke [51,52], brain injury [53] and other neurological diseases [54,55]. Glymphatic system visualization is not only implemented in animal studies [56,57], but also being used for clinical imaging diagnosis of hydrocephalus [58,59] and AD [60].…”
Section: Discussionmentioning
confidence: 95%
“…Neurodegenerative diseases are often associated with age [70]. Throughout life, the human brain accumulates different proteinaceous aggregates, such as Tau and Aβ.…”
Section: Neurodegenerative Diseases: Hypothesis Of Pathologic Synergymentioning
confidence: 99%